Socio-Demographic Processes in the Russian Arctic in Statistical Assessments and Population Surveys - Tatiana P. SKUFINA; Vera P. SAMARINA; Sergey V. BARANOV; Ekaterina А. BAZHUTOVA (Arctic and North, 2021)
Specificity of modern social processes determines close attention of the global scientific community to socio-demographic processes in the Arctic. The article examines systemic and recent social and demographic processes in the Russian Arctic, determined both by the immanent specifics of the Arctic (generating active migration processes, the phenomenon of city-forming enterprises, etc.) and by the all-Russian social reforms (in particular, the pension reform). The methodological peculiarity of the article is to present socio-demographic processes through the analysis of quantitative indicators, as well as through the reflection in the consciousness of the Arctic population (highlighting workers of city-forming enterprises) of modern factors of influence that determine their attitude to residence and work in the Arctic. The analysis of the results of settlement processes in the Arctic regions has been carried out, indicating an unstable stabilization of the population situation in the Nenets, Chukotka and Yamalo-Nenets okrugs, provided by various factors; it revealed the preservation of the negative trend of population decline in the Murmansk Oblast. Statistical analysis and surveys have revealed socio-demographic problems caused by the pension reform, which can aggravate the problem of the outflow of working-age population from the Arctic territories. It was found out that the reaction of city-forming enterprise employees differs from the "all-Arctic" reaction of the population on the grounds confirming the stabilizing role of city-forming enterprises in socio-demographic processes in the Arctic.